2017
DOI: 10.4172/2376-0354.1000194
|View full text |Cite
|
Sign up to set email alerts
|

Third Center of Domestication: Interaction between Genetics and Archaeological Sciences in Lands Devoted to Biodiversity of Grapevine Varieties

Abstract: Genetic research into grapevines identifies the Third Center of Variety Domestication in central-southern Italy. The many stories written "on wine", even though molecular archaeology, do not mention it. Here we present the application of a different analytical system. Archaeology introduces into Genetics the components of Space (places and materials) and Time (documented history). The genetic relationships of vine varieties combine with those who identified them, places devoted to cultivation and containers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Akram et al [2] found that, application of 100 kg ha -1 Phosphorus and 120 kg ha -1 Potassium to the chili plants resulted in optimal plant height; increased number of branches, leaves, flowers, and fruits per plant; enhanced fruit length, girth, and weight; enhanced seed weight and Phosphorus percentage. Lungo [3] conducted a study on the origin of grapevines, where grapevine varieties are annotated in history with their names and not by a generic reference notation. Ali and Mehmood [4], performed micro-propagation of Banana in Pakistan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Akram et al [2] found that, application of 100 kg ha -1 Phosphorus and 120 kg ha -1 Potassium to the chili plants resulted in optimal plant height; increased number of branches, leaves, flowers, and fruits per plant; enhanced fruit length, girth, and weight; enhanced seed weight and Phosphorus percentage. Lungo [3] conducted a study on the origin of grapevines, where grapevine varieties are annotated in history with their names and not by a generic reference notation. Ali and Mehmood [4], performed micro-propagation of Banana in Pakistan.…”
mentioning
confidence: 99%
“…The grape cultivars were later spread from Georgia, to the Middle-East, the Near-East, and Central Europe, which constituted the secondary domestication centers. According to Lungo [3], genetic research identifies central-southern Italy as the 'Third Center of Grape Domestication' , which represents the third stage of the journey of the vine varieties (Vitis vinifera L.) and vine related culture (ability to domesticate, cultivate, select, and spread) either together ('demic diffusion') or separately ('cultural diffusion') from the Caucasus to the Western world. However, molecular archaeology studies do not give any credence to it.…”
mentioning
confidence: 99%